Associations between a Leader's Work Passion and an Employee's Work Passion: A Moderated Mediation Model - Li, Jingjing; Zhang, Jian; Yang, Zhiguo (Frontiers in Psychology, 2017)
Based on the theory of emotional contagion and goal content, this study explored the positive associations between a leader’s work passion and employees’ work passion. This study investigated 364 employees and their immediate leaders from China, constructed a moderated mediation model, and used SPSS-PROCESS in conjunction with the Johnson-Neyman technique to analyze the data. The results showed that a leader’s work passion was transferred to employees via emotional contagion, and the contagion process was moderated by leader-employee goal content congruence. This study provides a potential way to stimulate employees’ work passion from the perspective of leader-employee interactions. Moreover, the limitations of the study and potential topics for future research are discussed.